REDESAIN PEMBELAJARAN TEMATIK PAI di ERA PENDIDIKAN 4.0 - Abas, Saehu; Susetiyo, Ari (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
This research discusses the thematic learning design of PAI in the era of education 4.0. His study was motivated by the presence of the phenomenon of education 4.0 which resulted in a learning system based on thematic islamic religious education must immediately get a touch of adjustment to the design of education 4.0. This research aims, to provide an overview or offer of thematic learning design of Islamic religious education using the theory and principles of educational science 4.0. This research uses a type of qualitative research with an approach using library research methods. The results showed that with the thematic learning design pai based on education 4.0, it can be processed planning patterns that are more in accordance with the theory and principles of education 4.0. Both seen from the type of learning communication approach, learning approach method and learning strategy. Second, pai thematic learning implementation pattern can be implemented by integrating elearning platforms from social media, integrating elearning platforms from video conference media, integrating elearning platforms from learning video media, integrating elearning platforms from digital literacy media, and integrating elearning platforms from task submit media. Finally, pai's thematic learning assessment system can take advantage of several platforms, such as Quiziz.com and Google Form.